PADUYA: SEBUAH KOMPOSISI MUSIK DALAM EUFORIA MAULUIK DI PADANG PARIAMAN, SUMATERA BARAT - Andika Bayu Putra; Asep Saepul Haris; Ediwar (Bajang Institute, 2021)
Paduya is the title of an archipelago music composition that originates from the phenomenon of community euphoria at a Mauluik event in Village Lareh Nan Panjang, District VII Koto Sungai Sariak, Padang Pariaman Regency, West Sumatera Province. Paduya is a form of enthusiasm from the community in celebrating Mauluik in Padang Pariaman Regency, so that the form of Mauluik celebration in Padang Pariaman Regency, especially Of Village Lareh Nan Panjang, is very much different from the Mauluik celebration in other areas, especially West Sumatra region. The contexts obtained from the research include; spirit, mutual cooperation, competition, and celebration. Effort are made to interpret the context is to make an analogy into the work of the musical compositions. The first part interprets the spirit and mutual cooperation of the community in the celebration of the Prophet's birthday with the title Sabiduak Sadayuang's. The second part is an attempt to interpret the existence of clashes, competitions, and social gaps with the title of Sejang's. In the third part, the form of interpretation of the Paduya. The metod of creation is done through literature study, observasion, studio work, and completion. The creation of this new work is obtained through the process of obseving an activity and is applied to the form of an archipelago music composition. The approach used is the tradition approach, Re-interpretation, and World Music. The purpose of the celebration of the Prophet Muhammad SAW’s birthday in Lareh Nan Panjang Village, District VII Koto Sungai Sariak, Padang Pariaman District, West Sumatera Province.